PENGARUH TRUST DAN GREEN MARKETING TERHADAP LOYALITAS PELANGGAN : STUDI EMPIRIS PADA LAYANAN TRANSPORTASI UMUM DI INDONESIA - Achmad Risal Basori; Supriyono; Dewi Deniaty Sholihah (Universitas Sarjanawiyata Tamansiswa, 2025)
Customer loyalty is a key factor in maintaining the desire of transportation service businesses amidst increasingly tight competition. This study aims to analyze the effect of trust and green marketing on customer loyalty in public transportation service, with a case study at PO. Gunung Harta in Bangkalan Regency. This study uses a quantitative approach with purposive sampling method, involving 83 respondents who are users of the service more than twice a year. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results of the study indicate that trust has a positive and significant effect on customer loyalty. Likewise, green marketing has a positive and significant effect on customer loyalty. These findings indicate that customer trust in service and the implementation of environmentally friendly marketing strategies play an important role in building and maintaining customer loyalty. Therefore, transportation companies are advised to continue to increase customer trust through transparent, safe and consistent service, as well as implementing sustainable green marketing practice.